Indústria 4.0: Colaboradores robóticos em cenários de logística - Lucas Santos Damas (2019)
In the last few decades, due to research and investment in robotics, robots have ceased to be fiction and have become reality. There are several types of robots that have been developed to run from the simplest to the most complex. The dissertation project simulates robots in a factory environment. There are two robots that are totally autonomous and will do the tasks requested by the control panel. There are 2 places of unloading where the final product will be delivered, 2 loading sites where the robots load the raw materials (in this project plastic bottles) and 3 manufacturing substations, where the 3 fill the bottles with different flavors, but different costs and random fluctuations within an acceptable range for the manufacture of water bottles. The robots have to transport the feedstock from the loading zone to the manufacturing substation zone and then from the factories to the discharges depending on the number of orders placed on the system control panel. The trajectories for each target location are pre-defined and optimized. Robots can't have collisions at all. These have a handle so they don't collide with the factory obstacles. Because the robot doesn't identify other robots, each robot receives the position and angle of the other robot and has to bypass. This project also has associated production and transport costs, as well as the simulation of possible faults. In this way, I can describe a manufacturing environment with cost optimization, bringing the project closer to reality. It is also implemented statistics of what will be done in the factory.